Overcoming urban stream syndrome: Trophic flexibility confers resilience in a Hawaiian stream fish. (8th March 2018) - Lisi, Peter J.; Childress, Evan S.; Gagne, Roderick B.; Hain, Ernie F.; Lamphere, Brad A.; Walter, Ryan P.; Hogan, J. Derek; Gilliam, James F.; Blum, Michael J.; McIntyre, Peter B.
Abstract: Urbanisation is widely associated with a suite of physical, chemical and biological degradation of stream ecosystems, known as "urban stream syndrome." It is unclear whether urban stream syndrome is applicable to oceanic islands, where marine dispersal of larvae enables diadromous species to continuously recolonise even highly degraded urban streams. The depauperate native fauna of oceanic island streams can be entirely composed of diadromous species, but urban streams food webs are often dominated by introduced predators, competitors and functional groups derived from continental systems. Despite these challenges, some native species appear to thrive in urbanised catchments. Here, we test for urban stream syndrome on oceanic islands by quantifying catchment land use, nutrient concentrations and fish community composition for 37 streams across the Hawaiian archipelago. To assess how native species adapt to food webs altered by species introductions, we quantified trophic responses by examining stomach contents, nitrogen stable isotopes and body condition of Awaous stamineus (an omnivorous goby) in each stream. Urbanisation was consistently associated with nitrogen pollution and replacement of native species with more tolerant exotics. Population densities of three of five native goby species declined sharply with urbanisation, whereas the two other native gobies species were resilient. The trophic position of the omnivore A. stamineus was elevated in urban streams compared to forested catchments, reflecting a shift in stomach contents from algae to greater reliance on exotic aquatic and terrestrial invertebrates. Comparable body condition and resilient population density of A. stamineus across the urbanisation gradient suggest that dietary flexibility buffers this species against environmental degradation. Our findings indicate that the concept of urban stream syndrome is applicable to oceanic islands, yet A. stamineus shows striking resilience. Flexibility in diet, life history and habitat use of this native goby appear to buffer it against the effects of urbanisation compared to most other amphidromous fishes in Hawaiian streams.